PENILAIAN KINERJA KEUANGAN PERBANKAN DI INDONESIA (STUDI KASUS PADA PT. BNI 46 CABANG MAKASSAR) - Abdullah Abdullah (AkMen JURNAL ILMIAH, 2014)
Banking Financial Performance Assessment in Indonesia (Case Study on PT. BNI 46 Branch Makassar), this study analyzed the financial performance of banks by using CAMEL (Capital, Assets, Management, Earnings, Liquidity), in this study, the researchers only assess aspects financial namely: Capital, Assets, Earnings, and Liquidity and did not assess aspects of Management. While Kriterian assessment used is based on Law No. 10 of 1998, and Bank Indonesia Circular Letter No. 6/23 / DPNP dated May 31, 2004 and Bank Indonesia Circular Letter No. 3/30 / DPNP dated 14 December 2001. The results of this study indicate that the aspect ratio of capital as measured by Capital Adequacy Ratio (CAR) is the predicate HEALTHY, because the value of the CAR above the minimum capital standards compliance obligations is above 8%. Aspects of asset quality as measured by the ratio of Troubled Assets (APB) is the predicate HEALTHY, because the value of the ratio of APB achieved not exceed 5%. Aspects of quality of productive assets as measured by the ratio of non-performing loan (NPL) is the predicate HEALTHY, because the value of the NPL ratio achieved under 5%. Aspects of profitability as measured by ROA and ROA are the predicate HEALTHY, because the value achieved ROA is above 1.25%, and ROA does not exceed 93.5%. Aspects of liquidity as measured by the LDR is the predicate LESS HEALTHY, this is because the LDR value achieved is between 100% - 120%.